(untitled) (Research, Society and Development, 2020)
Integrative Community Therapy (ICT) is a light technology of group care adaptable to different environments, populations and contexts. In this period of the COVID-19 pandemic, the ICT adapted itself to the virtual environment and brought together members of the community in the period of social isolation in the collective construction process of care. It is about this experience that this work intends to discuss. This study has a qualitative, descriptive and exploratory approach, with a view to presenting results of a research that addresses the concerns and confrontation strategies of the participants of the virtual ICT experiences, carried out during the pandemic period and respective social isolation. The ICT meetings were conducted in pre-determined stages: reception, choice of the theme, contextualization, problematization, aggregation rituals and positive connotation. The therapists performed participant observation and registered the written information. Eight virtuais meetings were held during the pandemic period, from 24th April to 10th July 2020, with a total of 112 participants, the majority of them students of the females’ gender. The speeches of the choice of the theme, contextualization and problematization stages were organized in the categories sensations, emotions, feelings and necessities, identified as: fear, anger, sadness, guilt, discouragement, anguish, anxiety, insecurity, concern and loneliness. The majority of the themes had relationships as a background. The samples of the participants’ speeches revealed different relational situations experienced and respective confrontation, overcoming and resignification strategies, among them were detected the promotion of self-care, self-awareness and the desire to understand and search for meanings.